Pemanfaatan Social Network Analysis Untuk Menganalisis Kolaborasi Komunikasi Pada Balai Perikanan Budidaya Laut Ambon - Latupeirissa, Ariyanto; Sediyono, Eko; Iriani, Ade (Universitas Diponegoro, 2019)
Marine aquaculture center-Ambon (Balai Perikanan Budidaya Laut/BPBL-Ambon) is a technical implementing unit under supervision of Directorate General of Aquaculture, Ministry of Maritime Affairs and Fisheries, Republic of Indonesia. Based on report of government’s internal control system (Sistem Pengendalian Intern Pemerintah/SPIP) specifically at the third quarter, some crucial organizational disadvantages have been identified in BPBL-Ambon, particularly related to the communication and coordination between divisions and technical staffs. To deal with this problem, there is a need to analyze and map the roles of interactions between employees in social networks. This study aims to analyze the patterns of interaction between staffs in the social networks. In this work, social network analysis (SNA) was used, which is based on formal and informal interactions on BPBL-Ambon, enabling to identify the key actors potentially able to act as alternative actors for information access to facilitate communication. The collection of individual data, as well as formal and informal interactions, was carried out using questionnaire and interview, involving entire population (saturation sampling). The collected data were then filetered and tabulated symmetric matrix, as preliminary steps for analysis following exported. SNA approach focuses on determining degree centrality, closeness centrality, and betweenness centrality. As a result, our experimental data suggested that most divisions alreadyshowed an appreciable collaboration in terms of communication; however, the remaining divisions showed 0 value in terms of their relationship with other divisions. Based on these findings, we could solve the problem through acting the alternative actors having the highest indegree value apart from stakeholders from a division capable of acting as alternative sources of information. The involvement of alternative actors could be a meaningful attempt in order to solve communication and coordination problems present in BPBL-Ambon